1938
DOI: 10.1017/s0022172400011219
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the bacterial flora of the hen's egg, with a description of new species ofProteusandPseudomonascausing rots in eggs

Abstract: 1. Examination of several hundred eggs suggests that a high proportion (98%) of the whites of fresh eggs, and a slightly smaller proportion of the yolks (93%), are sterile.2. The shell of the egg is heavily infected with a heterogeneous flora, includingProteusandPseudomonasbacteria capable of producing rotting.3. The rots found in imported New Zealand and Australian eggs, and in English stored eggs, may be grouped into black rot, red rot, green rot, and a miscellaneous group.4. Black rot is brought about chief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

1940
1940
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 11 publications
3
35
0
Order By: Relevance
“…The average total count of aerobic and Gram-negative bacteria of the 20 eggs analysed within 2 h after sampling deviated respectively less than 0.01 and 0.04 log cfu/eggshell compared to the other 20 eggs of the same batch analysed after 56 h storage in ambient conditions in the laboratory. Also Haines (1938) reported no significant difference in the bacterial flora on the egg between eggs examined immediately and after keeping for 4 days at room temperature.…”
Section: Collection and Transport Of Eggsmentioning
confidence: 94%
See 3 more Smart Citations
“…The average total count of aerobic and Gram-negative bacteria of the 20 eggs analysed within 2 h after sampling deviated respectively less than 0.01 and 0.04 log cfu/eggshell compared to the other 20 eggs of the same batch analysed after 56 h storage in ambient conditions in the laboratory. Also Haines (1938) reported no significant difference in the bacterial flora on the egg between eggs examined immediately and after keeping for 4 days at room temperature.…”
Section: Collection and Transport Of Eggsmentioning
confidence: 94%
“…One method concerned removal of the egg content and crushing of the shell and shell membranes in a sterile plastic bag with 10 ml quarter-strength Ringer's solution (Ringer Solution, Oxoid, Hampshire, UK) for 2 times 1 min with an interval of 5 min rest in between (Haines, 1938). Another method considered the washing of intact eggs in a sterile plastic bag with 10 ml diluent.…”
Section: Determination Of Bacterial Eggshell Contaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is hypothesised that bacterial contamination of the egg content could result from the penetration of the shell by bacteria deposited on the surface of the egg after it has been laid; this is also called the horizontal infection route (Haines, 1938;Harry, 1963;Quarles et al, 1970;Schoeni et al, 1995). Smith et al (2000), Messens et al (2005;2006;2007) and De Reu et al (2006b;2006f) reported that increasing numbers of micro-organisms on the eggshell consequently increase the risk of microbial eggshell penetration and egg content contamination.…”
Section: Introductionmentioning
confidence: 99%